The KEPRAKTISAN MEDIA MATH SNAKE PADA MATA PEMBELAJARAN MATEMATIKA KELAS 5 SEKOLAH DASAR - Elisabeth Gebrillia Loupatty; Ni Luh Sakinah Nuraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary schools still faces various obstacles, including low motivation and student engagement due to the use of less varied learning media. This condition requires innovative, interesting, and easy-to-use learning media to support the learning process. This study aims to determine the practicality of the Math Snake learning media in fifth-grade elementary school mathematics. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The practicality test was conducted on 30 fifth-grade elementary school students after using the Math Snake media in mathematics learning. Data collection was carried out using a student response questionnaire consisting of 20 statements, then analyzed using quantitative descriptive analysis techniques by calculating the percentage of the media's practicality level. The results showed that the Math Snake learning media obtained a practicality percentage of 79.63% with a practical category. These results indicate that the media is easy to use, has an attractive appearance, and is able to increase student activity and enthusiasm during the learning process. Thus, the Math Snake media is suitable for use as an alternative learning medium for fifth-grade elementary school students.